2013
DOI: 10.1093/carcin/bgt005
|View full text |Cite
|
Sign up to set email alerts
|

The HLJ1 -targeting drug screening identified Chinese herb andrographolide that can suppress tumour growth and invasion in non-small-cell lung cancer

Abstract: HLJ1 is a novel tumour suppressor and is a potential druggable target for non-small-cell lung cancer (NSCLC). In this report, using a promoter-containing enhancer region as the HLJ1-targeting drug-screening platform, we identified several herbal compounds from a Chinese herbal bank with the capacity to enhance HLJ1 promoter activity and suppress tumour growth and invasion of NSCLC. Among the herbal drugs identified, the andrographolide (from Andrographis paniculata [Burm. f.] Nees.) most significantly induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Two herbal chemicals, curcumin (Chen et al, 2008) and andrographolide (Lai et al, 2013), were shown to induce HLJ1 expression and suppress tumorigenesis in lung adenocarcinoma and nonsmall cell lung cancer, respectively. High concentration of DMSO ( ‡1%) was also shown to induce HLJ1 and inhibit malignant properties of lung adenocarcinoma cells (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two herbal chemicals, curcumin (Chen et al, 2008) and andrographolide (Lai et al, 2013), were shown to induce HLJ1 expression and suppress tumorigenesis in lung adenocarcinoma and nonsmall cell lung cancer, respectively. High concentration of DMSO ( ‡1%) was also shown to induce HLJ1 and inhibit malignant properties of lung adenocarcinoma cells (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, HLJ1 (DNAJB4) belongs to the DNAJ (HSP40) family of HSPs and is regarded as a tumor suppressor gene in lung, colon, and gastric cancers (Liu et al, 2014;Simões-correia et al, 2014;Tsai et al, 2006;Wang et al, 2005). HLJ1 has also been suggested as a potential biomarker and therapeutic target in lung cancer (Chen et al, 2008;Lai et al, 2013;Tsai et al, 2006;Wang et al, 2007). Moreover, in vitro studies showed that induction of HLJ1 inhibits cancer cell invasion in hepatocellular carcinoma cells (Wang et al, 2007).…”
mentioning
confidence: 99%
“…Therefore, while these inhibitors do not bind directly to Hsp40, they provide a proof of concept for the disruption of the Hsp70 chaperone through inhibition of Hsp40 binding. The natural product andrographolide, isolated from a Chinese herb, is another natural compound that influences the function of Hsp40 [138]. This compound was identified in a screen of natural compounds with the ability to activate the promoter of the Hsp40 protein DNAJB4.…”
Section: Naturally Occurring Inhibitorsmentioning
confidence: 99%
“…Using the HLJ1 promoter and luciferase reporter assays, the HLJ1-targeting drug-screening platform was established to screen and identify traditional Chinese herbs that can target the novel tumour suppressor gene HLJ1. Among the herbal drugs identified, the andrographolide is a promising new anticancer agent that could significantly induced HLJ1 expression and suppress tumour growth and invasion in NSCLC [90] . Andrographolide, a diterpenoid lactone isolated from the Chinese herbal medicine Andrographis paniculata, is known for its wide pharmacological activities, such as its anti-inflammatory, antiangiogenesis, pro-apoptosis and anticancer activities [91] .…”
Section: Hlj1 As a Molecular Target In Anticancer Therapiesmentioning
confidence: 99%
“…Using this platform, we identified andrographolide as a promising new anticancer agent that could suppress tumour growth and invasion in NSCLC. The onco-suppressive effects of andrographolide may be partially mediated by JunB-regulated HLJ1 expression, which modulates the transcription factor AP-2α binding at the MMP2 promoter and represses the expression of MMP2 [90] . In addition, silencing HLJ1 partially reverses the inhibition of cancer cell invasion by andrographolide.…”
Section: Hlj1 As a Molecular Target In Anticancer Therapiesmentioning
confidence: 99%